Awkward Prods: biographical studies of Progressive Protestants and political allegiance in Northern Ireland. Issue 2 (3rd April 2018) - Greer, James; Walker, Graham
ABSTRACT: Through studies of four individuals, this article will explore the utility of biography as a method of disentangling strands of political allegiance in Northern Ireland during the era of the 'old Stormont'. The four individuals – Harry Midgley, Arthur Linden Agnew, Albert McElroy and Jack Hassard – are connected by progressive strands of political activism, Protestantism and use of Ulster-Scots or British identity to support their political stances. These four lives reveal much about the development of Northern Labour and Liberal politics, but as a collective biography, rather than a party or institutional history, they reveal much of the wider milieu of reformist Northern Protestants. Their diverse final political destinations highlight the tensions within this strand and the persistence of divisions in Northern Ireland.